Cyclic microwave-assisted spray synthesis of nanostructured MnWO4 - Thongtem S. (2014)
MnWO4 with nano-plates in flower-like clusters was produced from the mists of the solutions containing MnCl2·4H2O and Na2WO4·2H2O at different pH values by 300-900 W cyclic microwave radiation. The phase was detected by XRD and SAED, and was in accordance with that of the simulation. The flowers were characterized using SEM and TEM, and their lattice planes using HRTEM. The vibration spectra were characterized using Raman and FTIR spectrometers. Their photoluminescence is at 409-420 nm. © 2009 Elsevier B.V. All rights reserved.